Ionic liquid-based synthesis of MXene. Issue 75 (19th August 2020) - Husmann, Samantha; Budak, Öznil; Shim, Hwirim; Liang, Kun; Aslan, Mesut; Kruth, Angela; Quade, Antje; Naguib, Michael; Presser, Volker
Abstract : MAX phases are etched using an ionic liquid–water mixture to produce titanium carbide MXenes. The process avoids the use of any acid. Abstract : MAX phases are etched using an ionic liquid–water mixture to produce titanium carbide MXenes. The process avoids the use of any acid. Hydrolysis of the fluorine-containing ionic liquid leads to the selective removal of Al, while the ionic liquid is intercalated in-between the transition metal carbide layers.